1996
DOI: 10.1016/0014-5793(96)00124-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of porcine kidney aminopeptidase P indicates the involvement of two critical histidine residues

Abstract: Aminopeptidase P (AP-P), purified to homogeneity from porcine kidney membranes, was completely inactivated by treatment with 0.2 mM diethylpyrocarbonate (DEP) at pH 7.0. Treatment of the modified enzyme with 20 mM hydroxylamine resulted in recovery of AP-P activity. The differential absorption of native and modified AP-P at 240 nm showed that DEP modified two histidyl residues per mol of AP-P. The substrates, bradykinin(1-5) and Gly-Pro-Hyp, and also the inhibitor, apstatin, could protect against DEP inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The histidine residues in polygalacturonase could ionize in the pH range 5-7. Histidine residues have been implicated in the structure and conformational dynamics of proteins [15,16]. Chemical modification studies and an analysis of the kinetic parameters as a function of pH in polygalacturonase have indicated the presence of an essential histidine [17,18].…”
Section: Discussionmentioning
confidence: 98%
“…The histidine residues in polygalacturonase could ionize in the pH range 5-7. Histidine residues have been implicated in the structure and conformational dynamics of proteins [15,16]. Chemical modification studies and an analysis of the kinetic parameters as a function of pH in polygalacturonase have indicated the presence of an essential histidine [17,18].…”
Section: Discussionmentioning
confidence: 98%
“…X-prolyl aminopeptidase has been iden tified as a zinc metalloprotease, but does not contain any of the known zinc binding sites that classify the zinc metalloproteases in distinct families (Hooper, 1994). It has been shown by chem ical modification that two histidine residues of X-prolyl amino peptidase are essential for catalytic activity (Lim and Turner, 1996). Four conserved histidine residues were identified in the porcine sequence (H403.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal signal sequence is underlined. Weight-matrix predictions [31] identify two possible cleavage points for the signal sequence, either at Gly 21 shown). There is a typical cleavable signal sequence at the Nterminus.…”
Section: Figure 1 Nucleotide and Deduced Amino Acid Sequence Of Pig Kmentioning
confidence: 99%
“…The present work represents the first example of the cloning of AP-P from a eukaryotic source. However, the sequence fails to reveal likely zinc-binding or catalytic residues, although chemical modification studies on the purified enzyme have indicated the presence of two critical histidine residues [21] whose location has yet to be determined. We are now in a position to initiate site-directed mutagenesis studies to identify these and other residues involved in the action of this new class of proteolytic enzyme.…”
Section: General Conclusionmentioning
confidence: 99%
See 1 more Smart Citation